Fighting aflatoxins: Reducing risks in Kenya's food chains - International Livestock Research Institute (International Livestock Research Institute, 2014)
This film tells the story of a four-year project that is mitigating and measuring the risk of mycotoxins in maize and dairy products for poor consumers in Kenya.